Wind tunnel flutter testing on a highly flexible wing for aeroelastic validation in the transonic regime within the HMAE1 project - Govers, Yves; Mai, Holger; Arnold, Juergen; Dillinger, Johannes K.S.; Pereira, Allan K.A.; Breviglieri Jr., Carlos; Takara, Edgard K.; Correa, Manoela S.; Mello, Olympio A.F.; Marques, Rodrigo F.A.; Geurts, E.G.M.; Creemers, R.J.C.; et al. (My University, 2019)
The aircraft manufacturer Embraer, the German Aerospace Center (DLR), the Netherlands Aerospace Centre (NLR) and German–Dutch Wind Tunnels (DNW) have tested an innovative highly flexible wing within an aeroelastic wind tunnel experiment in the transonic regime. The HMAE1 project was initiated by Embraer to test its numerical predictions for wing flutter under excessive wing deformations in the transonic regime. A highly elastic fiberglass wingbody pylon nacelle wind tunnel model (see Figure 1), which is able to deform extensively, was constructed for the experiment. The model was instrumented with a large number of pressure orifices, strain gauges, stereo pattern recognition (SPR) markers and accelerometers. The wing was tested from Ma = 0.4 to Ma = 0.9 for different angles of attack and stagnation pressures. The static and dynamic behavior of the wing model was monitored and a new method to analyze its eigenfrequencies and damping ratios was used. In the past, the large amounts of data acquired during such experiments could only be evaluated with a time lag. An efficient method developed by DLR now allows performing the data analysis in real time [1, 2]. As a result, it was possible during the test to identify exactly which safety margins remained before the onset of flutter and the resulting possible destruction of the model.